Resting heart rate, guilt, and sympathy: A developmental psychophysiological study of physical aggression. (1st July 2017) - Colasante, Tyler; Malti, Tina
Abstract: Although low resting heart rate has been linked to frequent aggressive conduct in childhood, little is known about the interaction of this biological risk with social emotions that protect against aggression across development. With a sample of 5‐, 8‐, and 12‐year‐olds ( N = 110), we tested whether the negative link between resting heart rate and physical aggression was offset by high guilt and sympathy. Caregivers reported their children's physical aggression and sympathy. Children's electrocardiogram data were collected while they viewed a nondescript video, after which they reported their guilt—or lack thereof—in response to vignettes depicting social transgressions. Lower resting heart rate was significantly associated with higher physical aggression in 5‐year‐olds who reported low—but not medium and high—levels of guilt, and in 8‐year‐olds with low—but not medium and high—ratings of sympathy. Neither guilt nor sympathy moderated the resting heart rate–physical aggression link in 12‐year‐olds. We discuss how social emotions may help children with low resting heart rates navigate social conflicts and avoid aggressive physical confrontations.